2001
DOI: 10.1073/pnas.121177998
|View full text |Cite
|
Sign up to set email alerts
|

Prospective measurements of dehydroepiandrosterone sulfate in a cohort of elderly subjects: Relationship to gender, subjective health, smoking habits, and 10-year mortality

Abstract: The decrease with age of the adrenal-secreted dehydroepiandrosterone sulfate (DHEAS) in serum has suggested that it may be causally related to longevity. For the PAQUID [People (Personnes) Aged (Agé es) About What (Quid, in Latin)] cohort of elderly subjects, we have previously reported higher DHEAS in men than in women, a decrease with age and, among men, a negative correlation between the DHEAS level and mortality at 2 and 4 years. Here, with an 8-year followup in 290 subjects, we show a global decrease of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 59 publications
5
97
1
Order By: Relevance
“…It has also been hypothesized that differences may be attributable to population variability. For example, the prospective study by Mazat et al (109), demonstrated that the relative risk of 8-year mortality associated with low DHEA-S was 3.4 times higher in males under 70 years compared with older men (odds ratios of 6.5 versus 1.9 respectively), suggesting substantial heterogeneity in this population according to age (109). Adjustment for BMI in most studies may have attenuated the relationship of DHEA-S to cardiovascular disease endpoints.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…It has also been hypothesized that differences may be attributable to population variability. For example, the prospective study by Mazat et al (109), demonstrated that the relative risk of 8-year mortality associated with low DHEA-S was 3.4 times higher in males under 70 years compared with older men (odds ratios of 6.5 versus 1.9 respectively), suggesting substantial heterogeneity in this population according to age (109). Adjustment for BMI in most studies may have attenuated the relationship of DHEA-S to cardiovascular disease endpoints.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The studies performed in women (Table 4) are very consistent in demonstrating that there is no relationship between plasma DHEA-S levels and mortality from cardiovascular disease or other causes. Indeed, no significant association was found in all seven population studies performed to date (105)(106)(107)(108)(109)(110)(111)(112). A trend for higher mortality rates in women with elevated DHEA-S was found in the study by Barrett-Connor & Khaw Gruen (110).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy remains largely unexplained. It could be due to the way that change is defined in each of the studies or to the influence of a regression to the mean phenomenon (8,9). Regression to the mean describes the tendency of high or low values of a biological marker to return towards the mean upon re-testing (10 -13).…”
Section: Introductionmentioning
confidence: 99%
“…DHEA treatment of older men and women has not been convincingly demonstrated to have significant clinical benefits, with the exception of a study by Morales et al (1994) showing improvement in self-reported physical and psychological well-being in post-menopausal women. DHEA may be a reliable biomarker of aging specifically in men (Roth et al, 2002) and a potential predictor of mortality (Mazat et al, 2001). Hornsby (1997) makes the case that the most likely function for DHEA is as a precursor for conversion to potent androgens, which mediate adrenarchy, a sexual signaling mechanism occurring just before puberty in higher primates.…”
Section: Dehydroepiandrosteronementioning
confidence: 99%